2008
DOI: 10.1517/14712598.8.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines to combat smoking

Abstract: Background-Current U.S. FDA approved biological therapies for treating smoking target central nervous system processes. Although these therapies have had some success, relapse within a year is still high. Clearly additional strategies are needed to aid individuals in maintaining abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…This finding implies that such a vaccination approach would be most effectively used in association with standard behavior modification and the use of other medications as a complementary approach to stop meth use and addiction. Some authors have suggested that vaccination could be used as a prevention strategy for at-risk individuals [13,38], whereas others have expressed some skepticism and urged extreme caution if such an approach is routinely adopted [26,39,40]. At least with vaccination as a preventative against meth abuse, our findings that vaccinated rats increase early meth intake suggests the latter perspective may be more appropriate.…”
Section: Discussionmentioning
confidence: 87%
“…This finding implies that such a vaccination approach would be most effectively used in association with standard behavior modification and the use of other medications as a complementary approach to stop meth use and addiction. Some authors have suggested that vaccination could be used as a prevention strategy for at-risk individuals [13,38], whereas others have expressed some skepticism and urged extreme caution if such an approach is routinely adopted [26,39,40]. At least with vaccination as a preventative against meth abuse, our findings that vaccinated rats increase early meth intake suggests the latter perspective may be more appropriate.…”
Section: Discussionmentioning
confidence: 87%
“…Nicotine vaccines are also promising alternatives for smoking cessation which are currently under investigation [Garwood and Potts, 2007]. They act sequestering nicotine from the bloodstream and consequently preventing its penetration into the central nervous system [Garwood and Potts, 2007;Bevins et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers have speculated about using a vaccine as a preventive in minors who do not smoke or who are experimenting with nicotine products. 15 Children and adolescents may be engaging in smoking initiation but are generally not yet combating addiction, whereas highly addicted individuals may still find satisfaction in smoking despite the vaccine’s physiological effects. Employing a vaccine for prophylactic purposes in children and adolescents who are not yet nicotine-dependent might therefore be a highly effective strategy in cutting smoking incidence at the national level.…”
Section: The Science Of Nicotine Vaccinesmentioning
confidence: 99%
“…Immunological therapies to help smokers stop smoking have shown promise in phase I and II trials; similar therapies could combat smoking addiction before it starts. 4 Nicotine vaccines are distinctive because they confer protection not against infection—the normal target for vaccines—but against enticing pleasures that lead to unhealthy behaviors. As a result, using them preventively in children would be likely to arouse some novel ethical concerns that should be addressed before the vaccines become commonly available and their off-label use as a preventive measure becomes a real option.…”
mentioning
confidence: 99%